Getting the story right growth, redistribution, and poverty alleviation in the Philippines - Balisacan, Arsenio M. (1997)
The available date on poverty are inadequate in informing policy discussions on the growth-inequity-poverty nexus in the Philippines. The approach employed to generate the data yields inconsistent ranking of spatial and intertemporal poverty standards for the Philippines. It employs these standards to examine the proximate causes of the changes in sectoral and spatial poverty from the mid 1980s to the early 1990s, focusing particularly on the relative impact of growth and distributional changes. It finds that, contrary to popular perceptions, recent episodes of growth have not been anti-poor. The bulk of the poverty reduction in recent years has come from the beneficial effects of growth on the poor, through the importance of growth in poverty alleviation varies greatly across administrative regions and sectors of the economy.
Includes bibliographical references (pages 35-37).
Keywords: Poverty -- Government policy; Economic development -- Philippines; Poor